Multimodal E-Mental Health Treatment for Depression: A Feasibility Trial - Mohr, David C; Duffecy, Jennifer; Jin, Ling; Ludman, Evette J; Lewis, Adam; Begale, Mark; McCarthy Jr, Martin (JMIR Publications, 2010)
BackgroundInternet interventions for depression have shown less than optimal adherence. This study describes the feasibility trial of a multimodal e-mental health intervention designed to enhance adherence and outcomes for depression. The intervention required frequent brief log-ins for self-monitoring and feedback as well as email and brief telephone support guided by a theory-driven manualized protocol. ObjectiveThe objective of this feasibility trial was to examine if our Internet intervention plus manualized telephone support program would result in increased adherence rates and improvement in depression outcomes. MethodsThis was a single arm feasibility trial of a 7-week intervention. ResultsOf the 21 patients enrolled, 2 (9.5%) dropped out of treatment. Patients logged in 23.2 ± 12.2 times over the 7 weeks. Significant reductions in depression were found on all measures, including the Patient Health Questionnaire depression scale (PHQ-8) (Cohen's d = 1.96, P < .001), the Hamilton Rating Scale for Depression (d = 1.34, P < .001), and diagnosis of major depressive episode (P < .001). ConclusionsThe attrition rate was far lower than seen either in Internet studies or trials of face-to-face interventions, and depression outcomes were substantial. These findings support the feasibility of providing a multimodal e-mental health treatment to patients with depression. Although it is premature to make any firm conclusions based on these data, they do support the initiation of a randomized controlled trial examining the independent and joint effects of Internet and telephone administered treatments for depression.